Effects of Early Bedside Cycle Exercise on Gastrointestinal Function in Intensive Care Unit Patients Receiving Mechanical Ventilation - Yu, Tingting; Cai, Fuliang; Jiang, Rong (Frontiers in Medicine, 2022)
Background: A prolonged stay in ICU is associated with gastrointestinal failure, which may have a destructive effect on functional status within 1 year after hospital discharge. It was aimed to investigate the effects of a daily exercise session, using a bedside cycle ergometer, on gastrointestinal functions, such as diarrhea, gastric retention, and vomiting, in patients with severe pneumonia who received mechanical ventilation (MV). Methods: The study was a randomized controlled trial, and its setting was the ICU of a tertiary hospital in Eastern China. A total of 102 critically ill patients who received MV were recruited only when their cardiorespiratory function was deemed stable to perform a bedside cycling exercise. Those patients were expected to spend a minimum of 7 days in the ICU stay. All subjects received respiratory physiotherapy and performed a daily standardized passive or active motion session of limbs. The patients were randomized into two groups, the treatment group, which were administered passive or active leg exercise intervention for twenty mins per day, using a bedside ergometer, and the control group, which did not. Gastrointestinal functions and the nutritional status of both groups were evaluated on the first, fourth, and seventh days of training and at discharge. Results: During the seven days of the study, the number of patients with diarrhea in the treatment group was significantly lower than that in the control group. By contrast, there were significantly more patients in the treatment group with increased bowel sounds. However, there was no significant difference in the number of patients with vomiting and gastric retention between these two groups. Moreover, when the patients were discharged from the hospital, the albumin level and lymphocyte count were significantly higher in the treatment group (P<0.05). In addition, the number of invasive ventilation days in the treatment group was less than that in the control group (P<0.05). While the ICU length of stay and total hospitalization time were not significantly different between the two groups. Conclusions: Early exercise training in critical ICU survivors who received MV enhanced the recovery of gastrointestinal functions and improved the patient’s nutrition status at hospital discharge.